Different information needs—The major reasons for calling the helpline when invited to colorectal cancer screening. (7th April 2022) - Fritzell, Kaisa; Kottorp, Anders; Jervaeus, Anna
Abstract: Introduction: This study pertains to the design of a decision aid (DA) to shed light on information and support needs in colorectal cancer screening, with the aim to explore the calling patterns to the Screening of Swedish Colons (SCREESCO) study's helpline. Methods: A cross‐sectional study was conducted with data from documented telephone calls to the SCREESCO study, including individuals, 59–60 years, randomized to colonoscopy or high sensitive faecal immunochemical test (FIT). Results: More than 2000 calls (women 58.5%; colonoscopy 59%) were analysed. Calling patterns: unsubscribing from screening, confirmation of participation, logistical concerns about the screening procedure, counselling, and FIT screening difficulties or in need of a new FIT test. Comorbidity was the most frequent reason for unsubscribing and most of the counselling calls included questions about the FIT test or the colonoscopy. Conclusion: Most of the calls to the helpline seemed to be related to individuals' lack of understanding about the organization of the screening programme and the screening procedure. Therefore, we find it important to further stress the tailoring part in our DA developing process, that is, provide limited information initially, with the possibility of access to more, if desired by the individual, still with respect to the individual's needs, health and digital literacy. Patient and Public Contribution: Individuals representing the public and invited to SCREESCO participated since we analysed their calls to the helpline. The findings will contribute to our continued work with the DA where the public will contribute and participate.